Acceptability and iron content of catfish-based wonton as a potential iron-rich snack - Nuning Marina Pengge; Nurul Hindaryani; Nur Hatijah (AcTion: Aceh Nutrition Journal, 2026)
Anemia remains a health problem among adolescent girls, partly due to low iron intakes. The development of snacks based on local ingredients that are rich in iron and acceptable in terms of their sensory properties is a potential approach. However, studies integrating acceptability evaluation and analysis of actual iron content in a single snack product are limited. This study aimed to analyze the acceptability and iron content of catfish wontons with variations in catfish and wood ear mushroom formulations. An experimental study with three formulations (F1B, F2B, and F3B) was conducted and tested on 25 trained panelists. Organoleptic data were analyzed using the Kruskal–Wallis test, followed by the Mann–Whitney U test at a 5% significance level. The iron content was analyzed using the ICP-OES method with replication. The results showed that formulation F3B had the highest level of acceptance. No differences were observed in color, aroma, and texture (p > 0.05); however, significant differences were observed in taste attributes (p < 0.05). The iron content in F3B was 2.22 mg/100 g, which is equivalent to approximately 14–15% of the daily iron requirement for adolescent girls. In conclusion, the F3B formulation has the potential to be an alternative source of iron based on local ingredients with good sensory acceptance. Further research is needed to evaluate the bioavailability and contribution of actual consumption to iron adequacy